Virtual Reality as a Tool for Inducing and Understanding Transformative Experiences - Stepanova, Ekaterina R.; Quesnel, Denise; Kitson, Alexandra; Prpa, Mirjana; Riecke, Bernhard E. (Psychonomic Society 58th Annual Meeting, 2017)
Profound, positive emotional experiences in life, such as witnessing natural wonders and phenomena, can lead to cognitive shifts and changes to moral attitudes. These experiences are, however, rare and thus understudied. The immersive potential of virtual reality (VR) present an opportunity to both induce and study such experiences. Our work explores the use of custom VR content, with the aim of facilitating a deeper connection between the participant and the Earth (the perspective shift). We propose that in this context, a transformative experience consists of 1. Perceptual change created via immersive VR; 2. Cognitive change realized in the feel of connectedness with the natural world; 3. Behavioural change realized through pro-social and pro-environmental behaviours. To measure the participant's perspective shift, we utilize this new evaluation framework combining physiological, implicit attitude, and observational behavioural measures in a mixed-methods study. The framework was informed by two pilot studies exploring the use of goose bumps (physiological) and an implicit association test as a measure of profound emotion, and consequently the feeling of interconnectedness.
Keywords: Riecke; Riecke_2017; alex-kitson; bernhard-riecke; denise-quesnel; earthgazing; katerina-stepanova; mirjana-prpa; motion cueing; motion-cueing; proj--motionCueingInterfaces; spatial updating; talkWithoutPaper